Spontaneous notification of adverse drug reactions - Laura Barrero Viera; Luis Alberto Bestard Pavón (Revista Cubana de Medicina Militar)
Introduction: The proper use of medications eliminates or controls numerous diseases, contributes to the well-being of the population and increases life expectancy; but it can also generate adverse reactions, which must be reported to identify new risks and build the true safety profile of any drug. A review of articles published in the databases LILACS, PAHO, SciELO, EMBASE, PubMed and Infomed, related to the subject is carried out. Objectives: To analyze the spontaneous notification process of adverse drug reactions in Cuba. Development: The Center for International Drug Monitoring, analyzes the patterns of alleged damage they cause throughout the world, based on reports sent by member countries, including Cuba, which, through the National Coordinating Unit of Pharmacovigilance, harmonizes activity at the national level. This process has as its cornerstone the person who reports, whether he is a healthcare professional or a patient, and spontaneous notification is the most frequent way, but which may find limitations in its development, on which it must be acted upon, to acquire knowledge and skills. necessary in the search, diagnosis, report, treatment, awareness of their need and motivation. Conclusions: The Cuban pharmacovigilance system has standardized its actions and working methods, spontaneous notification of adverse drug reactions is its most important source of information. Its limitations and the way to systematically eradicate them have been identified.